Exploring the therapeutic alliance in mental health care for people with serious mental illness: A focus group study with clients, care professionals, and peer support workers - de Jong, Steven; Bruins, Jojanneke; Hasson-Ohayon, Ilanit; Castelein, Stynke (Journal of Recovery in Mental Health)

(untitled) (Ontario Shores Centre for Mental Health Sciences, 2025)
Objective: A good therapeutic alliance (TA) positively influences many outcomes in the treatment of people with severe mental illness (SMI). However, there is little evidence-based advice on how to build and maintain a good TA with SMI clients, with clients' perspectives largely missing from current literature.Research Design and Methods: The views of clients, peer support workers (PSW) and other mental health care professionals (MHCP) on the TA in multidisciplinary mental health care teams are investigated through 13 open-ended focus groups with three separate types of stakeholders: clients, PSWs and other MHCPs from five Dutch psychiatric institutes. Transcriptions were analyzed qualitatively using grounded theory, with an open coding approach and inductive thematic analysis.Results: In the collected data, four main domains were identified: authenticity, trust and reliability, shared treatment goals and availability. To build a good TA all parties should communicate transparently and MHCPs should be reliably available, listen actively to the needs of the client and build trust before discussing treatment goals. Showing authentic interest helps maintaining a good TA, as well as adapting to clients’ changing needs, stability in contact and being available in case of need.Conclusions: Investing in long-term TA is needed, which can be achieved by building trust over time, being available as a team and by genuinely listening to a client in order to understand and find agreement on their treatment goals. Clients’ needs with regard to the TA may change while they move through various stages of recovery, to which MHCP should adapt.